Secondary Repair of the Zygoma - Orzell, Susannah; Yanik, Susan; Tatum, Sherard A. (Facial Plastic Surgery, 2017)
Secondary deformities of the zygoma are a rare entity, thanks to the adoption and refinement of open reduction and internal fixation techniques. These injuries are often difficult to treat due to the unique structural, functional, and aesthetic properties of the zygoma. Purely cosmetic defects can often be managed with implants; however, functional deficits generally require mobilization, correction, and subsequent fixation of the defect(s). Performing the necessary osteotomies to mobilize the zygoma is the most crucial part of the procedure, and had traditionally been executed without the use of computer aids. Planning for and performing this step was very difficult and frequently resulted in unsatisfactory outcomes. Recent advancements in virtual mapping and planning have obviated the need for guesswork and have resulted in improved functional and aesthetic outcomes following repositioning. This article will discuss the use of implants, osteotomies, and computer-assisted design/modeling (CAD/CAM) in addressing secondary deformities of the zygoma.
Keywords: zygoma; zygomaticomaxillary complex; fracture; secondary deformity; trauma